Neuroprotective Effects of Total Steroid Saponins on Cerebral Ischemia Injuries in an Animal Model of Focal Ischemia/Reperfusion - Zhang, Xinxin; Chen, Lin; Dang, Xuan; Liu, Jianli; Ito, Yoichiro; Sun, Wenji (Planta Medica, 2014)
Total steroid saponins isolated from Dioscorea zingiberensis are a unique traditional Chinese medicine known for its potential usage in various types of diseases. However, there is little evidence about its neuroprotective effect in transient focal ischemia-reperfusion cerebral injury. Therefore, the current study was carried out to investigate the effect of total steroid saponins on neuroprotection and its potential mechanisms in the rat ischemia-reperfusion model by middle cerebral artery occlusion for 90 min. The rats were each treated with total steroid saponins (30 mg/kg, 10 mg/kg, and 3 mg/kg) or nimodipine (20 mg/kg) daily for 6 days before middle cerebral artery occlusion. Then, the neurological deficit score, cerebral infarct volume, and brain water content were measured at 24 h after reperfusion. Meanwhile, the histopathological changes and AQP-4 protein activities were examined in hippocampal CA1 and the cortex of ipsilateral ischemic cerebral hemisphere by hematoxylin-eosin staining and immunohistochemistry, respectively. The indices of oxidative stress in the serum were also obtained, and NF-κB and ERK 1/2 protein expressions in the injured brain were evaluated by Western blotting. The results indicated that the pre-treatment with these drugs not only significantly reduced cerebral infarct volume, brain water content and improved neurological deficit score, but also restored neuronal morphology and decreased the AQP-4 positive cells in CA1 and the cortex. Moreover, it markedly restored the level of oxidant stress markers (CAT, SOD, MDA, NO and iNOS) to their normal range in serum. In addition, the increased NF-κB and ERK 1/2 protein expressions were alleviated as compared with the ischemia-reperfusion group. These findings demonstrate that total steroid saponins exhibit promising neuroprotection effects against the transient focal ischemia-reperfusion cerebral injury in the rat experimental model and the underlying mechanisms might be mediated through inhibition of anti-edema as well as anti-oxidative effects by inactivation of NF-κB and ERK 1/2 signalling pathway.
Keywords: Dioscorea zingiberensis; Dioscoreaceae; steroid saponins; middle cerebral artery occlusion; ischemia-reperfusion; anti-edema; anti-oxidative